Development of Integrative Medicine Therapy for gastrointestinal autoimmune diseases: a study protocol for a registry study - Cheol-hyun Kim; Kang-keyng Sung; Do-hyeon Kim; Hongmin Chu; Geon-hui Kang; Yeon-ju Moon; Hye-ryung Shin; Sangkwan Lee (Integrative Medicine Research)
Background: Although the incidence of autoimmune diseases (AD) increases every year, there is no effective therapy for it yet. This causes high medical costs to be spent on the management of autoimmune patients every year. The aim of this study is to identify the characteristics related to the causes and symptoms of gastrointestinal AD by collecting patients’ information and to further contribute to the development of an integrative medicine therapy for gastrointestinal AD. Methods/design: This study is a registry study of patients diagnosed with gastrointestinal AD. Subjects who voluntarily sign a written consent form after receiving a sufficient explanation will be assessed for compliance with the inclusion and exclusion criteria through a screening process on their first visit. A total of 35 subjects will be recruited; 15 will be assigned to the patient group, 10 to the control group, 8 to the caregiver group, and 2 to the medical staff group. The clinical information of the subjects will be evaluated through statistical analyses. As this study is a registry study, it will not test specific hypotheses. Discussion: If this study identifies the significant characteristics of gastrointestinal AD patients, the results will be useful for the development of integrative medicine methods for the treatment of gastrointestinal AD. Study registration: This study was registered with the Clinical Research Information Service (CRIS) of the Korea National Institute of Health (NIH), Republic of Korea (KCT0003976, date of registration: May 23, 2019). Keywords: Gastrointestinal autoimmune disease, Integrative medicine therapy, Protocol, Registry study